Comparison of Possibilities of UAV and Landsat in Observation of Small Inland Water Bodies - Pásler Miroslav; Komárková Jitka; Sedlák Pavel (Infonomic Society, 2015)
The paper evaluates possibilities of using Unmanned Aerial Vehicles (UAV) in observation of inland water bodies with focus on water quality in the future. Already used approaches of sensing water and its quality are briefly described in the beginning. A comparison of possibilities of observations based on Landsat data and based on UAV data is provided, attention is namely paid to temporal resolution, spatial resolution, influence of weather conditions and connected costs. Specific characteristics related to utilization of UAV in comparison with Landsat are stated. Possibilities of using UAV are demonstrated in the case study: observation of ponds near Pardubice in the visible part of electromagnetic spectrum. Landsat 7 and Landsat 8 data are used within the case study and a small UAV.
Porovnání možností UAV a Landsat při pozorování malých vnitrozemských vodních těles
Keywords: UAV; water; Landsat; cloud cover; remote sensing; UAV; voda; Landsat; oblačnost; dálkový průzkum